Cell-type specific activity of two glucocorticoid responsive units of rat tyrosine aminotransferase gene is associated with multiple binding sites for C/EBP and a novel liver-specific nuclear factor. - Grange, T (1991)
The structures of two remote glucocorticoid responsive units (GRUs) that cooperatively interact to promote cell-type specific glucocorticoid induction of rat tyrosine aminotransferase gene expression have been analyzed. DNAase I footprinting and gel mobility shift analyses reveal a complex array of contiguous and overlapping sites for cell type-specific DNA binding proteins. Apart from the glucocorticoid receptor, two liver-specific nuclear factors possess multiple binding sites in each of these GRUs: C/EBP and a newly identified liver-specific factor: HNF5. C/EBP possesses four binding sites in each GRU; a DNA-binding protein with similar binding specificity has been identified in fibroblasts; this protein could be related to AP-3. HNF5 possesses two binding sites in one GRU and four in the other. There are also HNF5 binding sites in numerous regulatory regions of other liver-specific genes. The interaction of HNF5 with DNA gives a characteristic DNAase I footprint with hypersensitive sites in the middle of the recognition sequence. Some of the C/EBP and HNF5 binding sites overlap in a conserved arrangement.